Angular distribution in two-body dissociation of SO2q+. Issue 15 (January 2020) - Rajput, J; Kumar, H; Bhatt, P; Safvan, C P
Synopsis: The two-body dissociation of multiply charged SO2 molecules is studied using a recoil ion momentum spectrometer. These molecular ions were generated in collision of the neutral parent with an energetic highly charged ion. From the measured momenta of the recoil ions, angular distributions are generated with respect to the incoming beam direction and are found to vary strongly with kinetic energy release.